1999
DOI: 10.1122/1.551018
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior and stability of concentrated silica suspensions

Abstract: In the present article, the rheological behavior and phase stability of concentrated silica suspensions were investigated experimentally by examining the effects of particle size and temperature. The silica particles were stabilized by adsorption of a silane coupling agent, ␥-methacryloxypropyl triethoxy silane ͑MPTES͒. The MPTES-coated silica particles behaved like hard spheres and exhibited the dispersion stability in tetrahydrofurfuryl alcohol which was used as a refractive-index matching solvent. For a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…For each sample, with increasing of shear rate, viscosity firstly decreased and then surged when critical shear rate was reached. The shear thinning at lower shear rate arises from transformation from three-dimensional ordered structure to a twodimensionally layered structure that permits continuous deformation (Lee et al 1999). As shown in Fig.…”
Section: Effect Of Concentrationmentioning
confidence: 98%
See 1 more Smart Citation
“…For each sample, with increasing of shear rate, viscosity firstly decreased and then surged when critical shear rate was reached. The shear thinning at lower shear rate arises from transformation from three-dimensional ordered structure to a twodimensionally layered structure that permits continuous deformation (Lee et al 1999). As shown in Fig.…”
Section: Effect Of Concentrationmentioning
confidence: 98%
“…The rheological properties of STF are influenced by various factors, such as the characteristics of dispersed particles (including the maximum packing fraction, type, shape, size, polydispersion, and interparticle action) and the solvents (Yu et al 2012;Maranzano and Wagner 2001;Maranzano and Wagner 2002;Lee et al 1999;Brown et al 2010;Chang et al 2011;Shenoy and Wagner 2005;Jiang et al 2010). Besides these parameters of the system itself, additives also exhibited great effect on ST behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We want to mention another rheological investigation, carried out by Lee et al (1999) on sterically stabilized silica particles in THFFA, in which they studied the onset of shear thickening as a function of the temperature. They suggested that the onset of shear thickening must be associated with an activation process, since the critical shear rate and the corresponding viscosity are straight lines in an Arrhenius plot.…”
Section: Comparison With Experimental Investigationsmentioning
confidence: 99%
“…Some examples are the glass transition or the crystal nucleation of hard spheres. For instance, poly(methylmethacrylate) and silica particles in organic solvents have been used to study glass formation and other aspects related to phase behavior of hard spheres and attractive spheres [1,2,3,4]. Polystyrene and fluorinated sphere systems have been employed to understand the effect of long-range repulsion on static and dynamic [5,6] properties, and also crystal formation [7].…”
Section: Introductionmentioning
confidence: 99%